2018
DOI: 10.1038/s41467-018-06133-0
|View full text |Cite
|
Sign up to set email alerts
|

Identifying weak interdomain interactions that stabilize the supertertiary structure of the N-terminal tandem PDZ domains of PSD-95

Abstract: Previous studies of the N-terminal PDZ tandem from PSD-95 produced divergent models and failed to identify interdomain contacts stabilizing the structure. We used ensemble and single-molecule FRET along with replica-exchange molecular dynamics to fully characterize the energy landscape. Simulations and experiments identified two conformations: an open-like conformation with a small contact interface stabilized by salt bridges, and a closed-like conformation with a larger contact interface stabilized by surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 61 publications
3
54
0
Order By: Relevance
“…This is further supported by the strong similarity of chemical shifts when comparing Xph15 and Xph20 binding to PDZ domain 1 alone and to the tandem. There should also be minimal impact on the dynamic interconversion of two major domain arrangements of the PDZ1 and PDZ2 domains that has been recently described 38 .
Fig. 4Docking models.
…”
Section: Resultsmentioning
confidence: 97%
“…This is further supported by the strong similarity of chemical shifts when comparing Xph15 and Xph20 binding to PDZ domain 1 alone and to the tandem. There should also be minimal impact on the dynamic interconversion of two major domain arrangements of the PDZ1 and PDZ2 domains that has been recently described 38 .
Fig. 4Docking models.
…”
Section: Resultsmentioning
confidence: 97%
“…S10). These experimental structures include, in particular, two chains of the same crystal structure from PDB (ID: http://www.rcsb.org/pdb/search/structidSearch.do?structureId=3GSL) , a structure determined by FRET presented by Bowen et al , and two further structures, an open‐like and a closed‐like conformation, resulting from the refinement of the same FRET structure by DMD simulations and presented by Sanabria and coworkers (5 structures in total).…”
Section: Resultsmentioning
confidence: 99%
“…Also, this study came to the conclusion that the same supramodular structure is maintained in the full‐length protein as in the isolated tandem . The FRET structure was subsequently refined with discrete molecular dynamic simulation and was found to be the average of many possible interdomain orientations, with two structures—an open‐like and a closed‐like conformation—emerging as the energetically most favorable ones . This study also identified the ultraweak interdomain interactions in the two most dominant conformations that stabilize the supramodular structure of the PDZ12 tandem.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Atomistic MD (molecular dynamics) simulations have been extensively used to investigate biomolecular complexes 18 . Several Recent studies have used MD simulations for understanding dynamics of ligand binding 19 , dynamics of multi PDZ domains 20 and allosteric interactions [21][22] associated with C-terminal peptide recognition by PDZ domains. However, internal peptide recognition has not been studied in detail.…”
Section: Introductionmentioning
confidence: 99%